7. Youth in Transition: Navigating Expectations in the Post-COVID Era - Potočnik, Dunja; Kuterovac Jagodić, Gordana; Rutar, Minea (Two Countries, One Crisis: The YO-VID22 Pandemic Study, 2025)
This chapter compares youth perceptions of societal norms in Croatia and Slovenia, revealing distinct mechanisms shaping their views. Croatian youth exhibit age-dependent patterns where growing autonomy influences the internalisation of societal expectations, leading to increasing self-confidence paired with a realistic reassessment of attainable life goals, particularly in education, housing, and financial independence. Slovenian youth, especially women, confront pronounced gender disparities rooted in structural inequities, burdening them with extensive societal and familial responsibilities. Both cohorts experience tension between individual aspirations and collective norms, with maturity prompting a shift from optimism to pragmatic evaluation of social milestones. Socioeconomic status (SES) strongly correlates with youths’ belief in personal success and adherence to societal expectations, with higher SES linked to greater confidence and internalisation, although national contexts mediate these effects. During the COVID-19 pandemic, age differences in justifying public health norms were minimal, but SES differences were significant, especially in Slovenia. Croatian youth showed less overall support for health measures but greater familial duty endorsement.